Pengaruh Variasi Intake Lobe Lift, Exhaust Lobe Lift Dan Celah Katup Terhadap Konsumsi Bahan Bakar Pada Sepeda Motor - Musa Wahyu Pangeran; Endry Meydiant; M. Agung Pribadi (Jurnal Energi dan Teknologi Manufaktur, 2020)
Motorbikes that are very much operated every day need fuel oil which is a fossil fuel that has been depleted and cannot be renewed. With the current conditions, it is necessary to control fuel consumption on a motorcycle. Setting the intake lobe lift, the exhaust lobe lift and valve gap have a positive impact on fuel consumption. There has been a lot of research about setting the intake lobe lift, the exhaust lobe lift and valve gap. The number of conventional motorcycle vehicles that are still operating requires special arrangements and deeper studies to be able to be economical in fuel consumption. The objectives of this study are: (1) to identify the factors that cause high fuel consumption. The research method uses the experimental method. By using pertamax. . The results showed that: 1) modification 2 uses the longest fuel consumption, and 2) there are effects of variations in the intake lobe lift and exhaust lobe lift on fuel consumption, 3) there is an effect of adjusting valve gap variations on fuel consumption, 4) there are the effect of variations in the intake lobe lift and exhaust lobe lift and adjustment of valve gap variations on fuel consumption.